2012
DOI: 10.1111/j.1365-2885.2012.01419.x
|View full text |Cite
|
Sign up to set email alerts
|

A physiologically based pharmacokinetics model for florfenicol in crucian carp and oral‐to‐intramuscular extrapolation

Abstract: In this study, an oral physiologically based pharmacokinetics (PBPK) model was developed for florfenicol in crucian carp (Carassius auratus). Subsequently, oral-to-intramuscular extrapolation was performed and the two models were used to predict florfenicol concentrations in the edible tissues of crucian carp. The oral model gave good predictions in most tissues, except for kidney and liver in which the florfenicol concentrations were underestimated at the later time points. In contrast, using the intramuscula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 24 publications
(99 reference statements)
1
35
1
Order By: Relevance
“…It is important to note that the steady‐state concentrations were attained following administration via the drinking water, while in the present model, danofloxacin was administrated by oral gavage. However, our previous study (Yang et al ., ) had shown that there were few differences in the P X s for a compound after different routes of administration in a particular species. In addition to these parameters mentioned previously, other parameters, such as partition coefficient of the ‘rest’ ( P r ), Cl re , Cl he , K a , and K gic were optimized using a maximum likelihood algorithm (Nelder–Mead) provided by the software of acslXtreme based on the plasma concentrations of danofloxacin after one single oral dose (Knoll et al ., ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is important to note that the steady‐state concentrations were attained following administration via the drinking water, while in the present model, danofloxacin was administrated by oral gavage. However, our previous study (Yang et al ., ) had shown that there were few differences in the P X s for a compound after different routes of administration in a particular species. In addition to these parameters mentioned previously, other parameters, such as partition coefficient of the ‘rest’ ( P r ), Cl re , Cl he , K a , and K gic were optimized using a maximum likelihood algorithm (Nelder–Mead) provided by the software of acslXtreme based on the plasma concentrations of danofloxacin after one single oral dose (Knoll et al ., ).…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, there has been an increase in the use of physiologically based pharmacokinetics (PBPK) model to estimate xenobiotics residue (Buur et al ., ; Yuan et al ., ; Leavens et al ., ; Yang et al ., , ,b, ,b). A PBPK model is a body composed of compartments, and each compartment contains mathematical equations describing the chemical's absorption, distribution, metabolism, and elimination (ADME).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, there has been an increase in the applications of physiologically based pharmacokinetic (PBPK) models to predict veterinary drug residues (Huang et al., ; Li, Gehring, Riviere, & Lin, ; Yang, Huang, et al., ; Yang et al., ; Yang, Sun, Liu, & Zeng, ; Yang, Sun, et al., ; Yang et al., ; Zeng et al., ). Compared with the traditional monitoring method after animal slaughter, the PBPK model is based on mass‐balance equations defined by physiological mechanisms, and it is predictive in nature and allows for the use of in vitro mechanistic data and population variability data to predict the distribution of drug in animals (Lin, Gehring, Mochel, Lave, & Riviere, ).…”
Section: Introductionmentioning
confidence: 99%
“…Florfenicol (FFC) is the second most frequently used antibacterial agent in Norwegian aquaculture (Samuelsen, Bergh, & Ervik, ). To our knowledge, in Asia, where the vast majority of aquaculture takes place, FFC is extensively used to treat pathogenic bacterial infections in aquaculture (Yang et al, ). As a broad‐spectrum chloromycetin‐series antibiotic, FFC is widely used in veterinary medicine.…”
Section: Introductionmentioning
confidence: 99%